Tire/road noise, texture, and vertical accelerations: Surface assessment of an urban road. (March 2020) - Vázquez, V.F.; Hidalgo, M.E.; García-Hoz, A.M.; Camara, A.; Terán, F.; Ruiz-Teran, A.M.; Paje, S.E.
Highlights: Some sections of the pavement with SMA8 stand out for their good acoustic performance. The relationship between macrotexture and tire/pavement noise has been studied. The macrotexture does not entirely explain the good acoustic performance. The acceleration spectrum shape depends on the pavement aging and conservation. Abstract: Pavements are made up of several layers with different mechanical and functional characteristics. The correct design of the surface layer of a road may lead to pavements with better characteristics regarding the ride quality and the safety, but also pavements that may reduce noise. The use of low-noise pavements may be an effective measure to reduce the acoustic pollution generated by road traffic. This work aims to assess some functional characteristics of a rehabilitated urban street, after two months in service conditions. The pavement was fabricated with a gap-graded bituminous mixture of Stone Mastic Asphalt (SMA) type with crumb rubber (CR) from end-of-life (EOL) tires. This work studies the acoustic performance of the pavement, as well as other surface characteristics, such as the macrotexture depth (MPD) and the unevenness (IRI), establishing the relationship between them and the tire/road noise at different frequencies. Finally, the main vertical acceleration frequencies of the pavement/vehicle system at a driving speed of 50 km/h are also assessed and related to the pavement unevenness and conservation. According to the results, this mixture might be used as a noise mitigation measure within the Action Plans of urban areas with problems related to noise. It is observed that the macrotexture depth of the mixture contributes to its acoustic performance at low frequencies; however, the tire/road noise generated cannot be totally explained from a macrotexture point of view.